Bilateral osteochondral defects of the patellae in an 11-year-old girl. Issue 4 (23rd April 2021) - Rodriguez Ruiz, Miguel; Igah, Ibidumo; Iranpour, Farhad; Patel, Akash
Abstract : Osteochondral defect or osteochondritis dissecans (OCD) of the knee usually affects young, active populations. It is a challenging diagnosis as patients typically present with poorly localised activity-related pain, which is non-specific and covers many differentials. We present an active 11-year-old girl with bilateral osteochondral defects of the patellae: a rare clinical disorder which was affecting her sporting activities. She had a 12-month history of bilateral anterior knee pain before the diagnosis was achieved with appropriate imaging. Her pain significantly improved with activity modification and physiotherapy. Follow-up will require outpatient clinic assessment and imaging to determine if non-operative management continues to be successful or surgery may be required. This case report emphasises the importance of appropriate high index of suspicion when managing patients with non-specific knee pain. It also demonstrates the importance of judicious use of imaging to avoid a missed or delayed diagnosis.